Nfluence of Parental Neglect on Mental Health of Children in Munuki Block Council Juba South Sudan - Suzan Alfred Tumalu (Uganda Christian University, 2025)
The research study focused on "The influence of parental neglect on the children mental health in Munuki Block Council." The research objectives were; To find out the forms of parental neglect in Munuki block council and To explore the mental health related challenges experienced by the children in Munuki Block council as a result of parental neglect. The researcher employed a qualitative research design to successfully carryout the research study.The purpose of study was generally aimed at establishing how parental neglect influences mental health of the children in Munuki Block Council Juba South Sudan. The study was carried out around the community of Munuki Block Council, South Sudan where there were many cases of mental illnesses. The cases of mental illnesses in Munuki Block Council were as a result of parental neglect among children. The Bamraund theory of parenting was employed by the research to have an assumed insights about parental neglect outcomes mental health of children in Munuki Block Council, South Sudan. The research findings included emotional, social and physical parental neglect as some of the forms of neglect. Inability to rely on support networks, avoidant behaviors and struggles in academic studies.The researcher concluded that issues concerning parental neglect on the mental health of the children requires monthly education since the neglect has been found to be common among parents of Munuki Block in South Sudan. The community leaders such as probation officers and schools especially the government schools together with the non-governmental organizations have to take on the role of educating the children and parents on the issues of parental neglect
Undergraduate